107 Developing effective leaders. (3rd November 2019) - Szram, Jo; Bailey, Emma; Thakrar, Priya; Thomas, Alex
Abstract : The Health Educational England London Leadership Development Steering Group produced and implemented the Spiral Leadership toolkit for all postgraduate medical and dental trainees in the London region. There is an urgent need to incorporate leadership development within the postgraduate training curricula to ensure the NHS has a robust pipeline of developing clinical leaders for 2020 and beyond. The NHS Long Term and interim People Plans call for healthcare organisations and specifically Health Education England (HEE) to support leadership development through training programmes, as part of curricular and professional capabilities. Until recently there has been a lack of available structure for trainees, their supervisors and faculties within NHS organisations and HEE itself to implement this requirement. The group examined available resources supporting the curriculum for future healthcare leaders and adapted an existing specialty school toolkit to make it widely applicable across all learner groups. A wideranging stakeholder exercise ensured comprehensive coverage of all learner and educator needs from foundation schools to trainees preparing for and starting out in their first few years of their consultant posts. Needs and resources were structured in a pragmatic and practical toolkit based around capabilities such as responding to a complaint, and leading a change project. The toolkit was reviewed by other regional leadership development leads for coherence across England. Educational leaders were upskilled in use of the toolkit and small-scale pilots in clinical oncology and dental training programmes started in 18/19. Other training programmes were given a 'soft launch' as part of annual induction, stressing the benefit to trainees. The toolkit is available to download online with an opt-in sign up for updates. Please see: https://www.lpmde.ac.uk/var/structure-of-training/spiral-leadership.